Exploring Science Teachers’ Perceptions and Practices in Integrating STEM and AI Through Mind Mapping: A Case Study in the UAE - Alneyadi , Saif; Almessabi , Ameera; Alshraifin, Nermien (Journal of Ecohumanism, 2024)
This study investigates the perceptions and practices of science educators regarding the integration of Science, Technology, Engineering, and Mathematics (STEM) with Artificial Intelligence (AI) through mind-mapping techniques within the context of the United Arab Emirates (UAE). Employing an exploratory sequential mixed-method design, the research comprises both qualitative and quantitative strands. The study addresses three primary research inquiries: (1) Approaches utilized by science teachers in integrating mind mapping techniques; (2) Perceptions and experiences of educators regarding the integration process; and (3) Extent of institutional support for implementing integrated STEM and AI education through mind mapping. Findings reveal positive outlooks among science teachers towards the efficacy of integrating STEM and AI through mind mapping, despite challenges such as initial technological learning curves and resource limitations. Recommendations include continuous professional development for educators and adequate resource allocation to address barriers.